EFFECT OF TEMPERATURE FIELD DISTRIBUTION ON THE CURVATURE CHANGE AND LAYER THICKNESS OF THIN-WALL PART FABRICATED BY LASER DIRECT METAL FORMING - Khoa, Doan Tat (Vietnam Journal of Science and Technology, 2016)
To discuss the effect of temperature field distribution on the curvature change and layer thickness of thin-wall parts, the numerical simulation and experimental was studied. The numerical results showed that the molten pool temperature of the thin-wall increases with the layer number, and the molten pool temperature of thin-wall cylinders were increases when decrease curvature radius; the rules of laser power changing with the layer number and curvature in the processing of the thin-wall blade can be obtained when keeping molten pool temperature stable. According to the numerical results, the thin-wall blades were fabricated by experiments. The experimental results showed that the excessive build-up occurred and unevenness thickness layer at small radius corner with constant laser power because of the increase of energy density at corners, with varied laser power is more uniform than the constant laser power, which is in agreement with the numerical simulation.